Online monitoring of gas transfer rates during CO and CO/H2 gas fermentation in quasi‐continuously ventilated shake flasks. Issue 5 (25th March 2021) - Mann, Marcel; Hüser, Aline; Schick, Benjamin; Dinger, Robert; Miebach, Katharina; Büchs, Jochen
Abstract: Syngas fermentation is a potential player for future emission reduction. The first demonstration and commercial plants have been successfully established. However, due to its novelty, development of syngas fermentation processes is still in its infancy, and the need to systematically unravel and understand further phenomena, such as substrate toxicity as well as gas transfer and uptake rates, still persists. This study describes a new online monitoring device based on the respiration activity monitoring system for cultivation of syngas fermenting microorganisms with gaseous substrates. The new device is designed to online monitor the carbon dioxide transfer rate (CO2 TR) and the gross gas transfer rate during cultivation. Online measured data are used for the calculation of the carbon monoxide transfer rate (COTR) and hydrogen transfer rate (H2 TR). In cultivation on pure CO and CO + H2, CO was continuously limiting, whereas hydrogen, when present, was sufficiently available. The maximum COTR measured was approximately 5 mmol/L/h for pure CO cultivation, and approximately 6 mmol/L/h for cultivation with additional H2 in the gas supply. Additionally, calculation of the ratio of evolved carbon dioxide to consumed monoxide, similar to the respiratory quotient for aerobic fermentation, allows the prediction of whether acetate or ethanol is predominantly produced. Clostridium ljungdahlii, a model acetogen for syngas fermentation, was cultivated using only CO, and CO in combination with H2 . Online monitoring of the mentioned parameters revealed a metabolic shift in fermentation with sole CO, depending on COTR. The device presented herein allows fast process development, because crucial parameters for scale‐up can be measured online in small‐scale gas fermentation.